Analytical modelling and analysis of magnet eddy current loss in magnet‐surrounded permanent magnet synchronous machine caused by stator slot effect - Long, Yuhang; Song, Zhanfeng (IET electric power applications, 2025)
To improve the machine torque density, this paper proposes a magnet‐surrounded permanent magnet synchronous machine (MSPMSM). As the critical material of MSPMSM, the permanent magnet (PM) will produce significant eddy current loss under the action of eddy current electromotive force. Therefore, it is essential to investigate the change in PM eddy current loss and methods to suppress it. To solve the above problems, a simplified analytical calculation model for the eddy current loss of PMs caused by stator slotting is proposed. The distribution law of eddy current loss of PMs caused by stator slotting is studied. The concept of influence depth is proposed to solve the problem of unclear correspondence between the groove depth on the PM surface and the eddy current loss of PMs. The calculation results of the influence depth are used to guide the single‐side partial grooving method to reduce the eddy current loss of PMs. In addition, a comparative analysis is conducted on the anti‐demagnetisation ability of PMs before and after MSPMSM optimisation. Finally, the experiment verifies the correctness of the analytical calculation and the high torque density of the MSPMSM.